Analisis literasi kesehatan pasien diabetes melitus tipe 2 dengan terapi oral antidiabetes di puskesmas Surabaya - Vidiani , Anak Agung Pradnya Paramitha; Puspitaningrum, Anisa Nova (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2023)
Introduction: Diabetes mellitus (DM) is a chronic disease requiring long-term therapy. Uncontrolled glucose levels can lead to micro and macrovascular complications as well as therapy failure. Medication adherence is a factor influencing the success of DM therapy. The aim of this study is to understand the adherence to oral antidiabetic drugs (OAD). Methods: This research employs a quantitative approach with a non-experimental cross-sectional design. The sample consists of all type 2 DM patients using OAD therapy at Surabaya Community Health Centers who meet the inclusion and exclusion criteria. Results and Conclusion: The health literacy level of Type 2 Diabetes Mellitus Referral Program patients who received Oral Anti-Diabetes therapy at the Surabaya Community Health Center in this study was 45% with high health literacy and 55% with low health literacy with a percentage of 55%. With the domains of patient attitudes towards health (72.50%), patient understanding of health information (57.50%), social support (22.50%), socio-economic considerations (75.00%), accessing health services (92.50%), 50%), communication with health workers (77.50%), pro-active (17.50%), and using health information (80.00%)